2007
DOI: 10.1590/s0100-204x2007000400016
|View full text |Cite
|
Sign up to set email alerts
|

Morfofisiologia e valor nutritivo do capim-braquiária sob sombreamento natural e a sol pleno

Abstract: Under shade, tiller population leaf area and forage mass index were higher in the second year than in the first. Forage neutral detergent fiber value was higher at full sunlight than in the shade, while the crude protein content and in vitro dry matter digestibility were higher under the trees. Moderate shading increases crude protein and reduces neutral detergent fiber, therefore improving forage digestibility of grasses growing under trees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
52
0
60

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 11 publications
(14 reference statements)
11
52
0
60
Order By: Relevance
“…This response in forages includes elongation of internodes and reduced tillering (Feldhake, 2001). The sunlight transmission values obtained in this study suggest that no significant damage occurred to the forage production, as the reduction of 35% of transmission (SP 2m ) is still within a tolerable range for the species (Paciullo et al, 2007;.…”
Section: Resultsmentioning
confidence: 60%
“…This response in forages includes elongation of internodes and reduced tillering (Feldhake, 2001). The sunlight transmission values obtained in this study suggest that no significant damage occurred to the forage production, as the reduction of 35% of transmission (SP 2m ) is still within a tolerable range for the species (Paciullo et al, 2007;.…”
Section: Resultsmentioning
confidence: 60%
“…Paciullo et al (2007) observed an increase in specific leaf area and a decrease in the leaf area index of B. decumbens pastures grown under shaded conditions in comparison to pastures grown under the open sunlight. A deep understanding of the morphological adaptations of grasses to environments with low light incidence represents a crucial step for the development of efficient management strategies aimed at silvopastoral areas, and at the long-term equilibrium of these ecosystems.…”
Section: Introductionmentioning
confidence: 82%
“…Marandú, 2,8 e 2,1 % maiores em área sombreada por Zeyheria tuberculosa do que em áreas de pastagem solteira. Já Paciullo et al (2007), em um SSP com Brachiaria decumbens, observaram teores de FDN 2,8% menores sob sombreamento do que a pleno sol.…”
Section: Sistemas Silvipastorisunclassified
“…Dentre os benefícios da adoção desses sistemas, podem ser destacados: aumento da eficiência de uso da terra; diversificação e aumento da renda por hectare; controle da erosão; aumento da fertilidade do solo pelo aumento das atividades biológicas e da ciclagem de nutrientes do solo e pela melhoria das características físicas; maior oferta de forragem com boa qualidade para os animais em função da melhoria da fertilidade do solo; flexibilidade no uso (corte precoce de árvores para escoras, lascas e lenha; corte mais tardio de árvores para produção de postes e de madeira para laminação; produtos florestais para uso na propriedade ou para comercialização; produtos florestais madeireiros e não madeireiros, como mel); e aumento da biodiversidade (CARVALHO et al, 2007).…”
Section: Sistemas Silvipastorisunclassified
See 1 more Smart Citation